Separation of the CaV1.2‐CaV1.3 calcium channel duo prevents type 2 allergic airway inflammation. Issue 2 (9th July 2021) - Giang, Nicolas; Mars, Marion; Moreau, Marc; Mejia, Jose E.; Bouchaud, Grégory; Magnan, Antoine; Michelet, Marine; Ronsin, Brice; Murphy, Geoffrey G.; Striessnig, Joerg; Guéry, Jean‐Charles; Pelletier, Lucette; et al.
Abstract: Background: Voltage‐gated calcium (Cav 1) channels contribute to T‐lymphocyte activation. Cav 1.2 and Cav 1.3 channels are expressed in Th2 cells but their respective roles are unknown, which is investigated herein. Methods: We generated mice deleted for Cav 1.2 in T cells or Cav 1.3 and analyzed TCR‐driven signaling. In this line, we developed original fast calcium imaging to measure early elementary calcium events (ECE). We also tested the impact of Cav 1.2 or Cav 1.3 deletion in models of type 2 airway inflammation. Finally, we checked whether the expression of both Cav 1.2 and Cav 1.3 in T cells from asthmatic children correlates with Th2‐cytokine expression. Results: We demonstrated non‐redundant and synergistic functions of Cav 1.2 and Cav 1.3 in Th2 cells. Indeed, the deficiency of only one channel in Th2 cells triggers TCR‐driven hyporesponsiveness with weakened tyrosine phosphorylation profile, a strong decrease in initial ECE and subsequent reduction in the global calcium response. Moreover, Cav 1.3 has a particular role in calcium homeostasis. In accordance with the singular roles of Cav 1.2 and Cav 1.3 in Th2 cells, deficiency in either one of these channels was sufficient to inhibit cardinal features of type 2 airway inflammation. Furthermore, Cav 1.2 and Cav 1.3 must be co‐expressed within the same CD4 + T cell to trigger allergic airway inflammation. Accordingly with the concerted roles of Cav 1.2 and Cav 1.3, the expression of both channels by activated CD4 + T cells from asthmatic children was associated with increased Th2‐cytokine transcription. Conclusions: Thus, Cav 1.2 and Cav 1.3 act as a duo, and targeting only one of these channels would be efficient in allergy treatment. Abstract : Each of Cav 1.2 and Cav 1.3 calcium channels plays a role in the full TCR‐induced activation of Th2 lymphocytes. Cav 1.2 and Cav 1.3 channels have concerted roles and must be co‐expressed within the same CD4 + T cell to trigger allergic airway inflammation. Expression of both channels by CD4 + T cells from asthmatic children is associated with increased Th2‐cytokine expression. Abbreviations: BM, bone marrow; Cav, voltage‐gated calcium channel; i.n., intranasal; TCR, T cell receptor; Th, T helper cell; WT, wild‐type